2018
DOI: 10.17015/ejbe.2018.021.06
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Financial Ratios and Market Stock Returns

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
4
22
0
6
Order By: Relevance
“…However, investors could still use this model to predict stock return in Jordan. These results are consistent with Allozi and Obeidat (2016), Afrino and Masdupi (2019), Kai and Abdrahman (2018), Musallam (2018), Din (2017), Stefano (2015), who suggested that the variance in stock return can be explained by accounting and market indicators and financial ratios.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, investors could still use this model to predict stock return in Jordan. These results are consistent with Allozi and Obeidat (2016), Afrino and Masdupi (2019), Kai and Abdrahman (2018), Musallam (2018), Din (2017), Stefano (2015), who suggested that the variance in stock return can be explained by accounting and market indicators and financial ratios.…”
Section: Discussionsupporting
confidence: 88%
“…The results are consistent with economic theory. This result is consistent with the findings of Kai and Abdrahman (2018) and Musallam (2018). Additionally, EPS had a statistically significant and positive impact on stock return, B = 0.009.…”
supporting
confidence: 91%
“…Companies that have high equity do not always produce high profits, but if the profits are large or small, they will not necessarily be allocated to stock returns. Low profit might be allocated to cover the company's debt interest (RM Musallam, 2018). Such conditions can be caused by external factors, namely declining economic conditions and internal factors of the company.…”
Section: Effect Of Profitability On Return Defensive Stocksmentioning
confidence: 99%
“…Asif et al (2016) also found that there is an ability for accounting information to predict the price of the stock, as it was found that the earnings per share, book value per share, the capital used per share and the operating cash flow per share have an impact on the market prices of corporate stocks. Musallam (2018) concluded that the earnings per share, earnings yield ratio, and dividend yield ratio have a large and positive relationship with fluctuations in the stock prices in the Qatari market, while the market to book value ratio, price to earnings ratio, dividends earnings ratio has a slight relationship with With fluctuations in stock prices. Otekunrin et al (2018) concluded that the earnings per share, net assets per share, debt ratio and return on asset ratio are positively and significantly related to the market prices of stocks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%